Pediatric Erosive Gastritis: A Case Report - Sulaiman Yusuf; Intan Chaharunia Mulya (Budapest International Research and Critics University, 2020)
Dyspepsia is a common gastrointestinal disorder which needs diagnostic examination test using endoscopy. Pediatric erosive gastritis, the case presented, is one of the diagnosis confirmed after endoscopy examination test which is mostly associated with Helicobacter pylori infection. A 10-year-old boy was presented to emergency department complaining cyclic vomiting, heartburn and constipation. Further inquiry revealed that similar progressive condition was also complained one year ago prompting endoscopy examination test to find out the underlying etiology. Erosive gastritis and Gastroesophageal Reflux Disease (GERD) were confirmed after examination. Investigation of Helicobacter pylori infection with fecal examination test was impossible due to constipation. Erosive gastritis is a gastric mucous inflammation commonly caused by Helicobacter pylori infection. The clinical manifestation of gastritis tends to be asymptomatic until a pathological component is found. Any pathology suspicion of the gastric lining may require further endoscopy examination test. The therapy of paediatric erosive gastritis includes Proton Pump Inhibitor (PPI), sucralfate sucralfate as also lifestyle modification could improve children’s condition. In conclusion, paediatric erosive gastritis is an organic disorder of gastric lining treated by Proton Pump Inhibitor (PPI), sucralfate and symptomatic agents for associated symptoms. Helicobacter pylori is often associated with erosive gastritis so that further examination is needed.